The Link between Circadian Clock Genes and Autophagy in Chronic Obstructive Pulmonary Disease. (25th October 2021) - Hu, Yuedi; He, Tiantian; Zhu, Jie; Wang, Xiaole; Tong, Jiabing; Li, Zegeng; Dong, Jingcheng
Abstract : Chronic obstructive pulmonary disease (COPD), a progressive respiratory disease, is characterized by the alveolar epithelium injury and persistent airway inflammation. It is documented that oscillation and dysregulated expression of circadian clock genes, like Bmal1, Per1, and Per2, involved in COPD pathogenies, including chronic inflammation and imbalanced autophagy level, and targeting the associations of circadian rhythm and autophagy is promising strategies in the management and treatment of COPD. Herein, we reviewed the mechanisms of the circadian clock and the unbalance of the autophagic level in COPD, as well as the link between the two, so as to provide further theoretical bases for the study on the pathogenesis of COPD.